Factors Associated with the Outcomes of Patients with Hospital-Acquired Pneumonia (HAP) at Dr. Moewardi General Hospital, Surakarta - Nawanindha, Natasha; Saptawati, Leli; Widyaningsih, Vitri (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: Hospital-acquired pneumonia (HAP) is a common infection with a poor prognosis. Previous studies on factors influencing HAP outcomes have yielded inconsistent findings. Therefore, further research is needed to determine risk factors that affect HAP outcomes. This study evaluated the factors associated with HAP outcomes to enable timely interventions to reduce mortality, costs, and length of stay (LOS). Methods: This cross-sectional study was conducted at Dr. Moewardi General Hospital, Surakarta, using medical record data from January to December 2022. The data included age, gender, malnutrition, anemia, level of consciousness, comorbidities, bacterial culture, and multidrug-resistant organisms (MDROs). The analyses were performed using the Chi-squared and Mann-Whitney U tests, followed by multiple logistic and linear regression tests to determine the correlation between risk factors and outcomes (recovery, death, and LOS). Results: This study included 102 patients with HAP, the majority being males (64.7%) aged 60 years old and above. Additionally, most patients did not exhibit malnutrition (87.3%) or anemia (96.1%), had normal levels of consciousness (67.6%) and mild comorbidities (60.8%), were not infected with MDROs (66.7%), and were predominantly infected by Klebsiella pneumoniae (21.6%). The multiple logistic regression test revealed that decreased consciousness was significantly associated with increased mortality (p < 0.001). Meanwhile, age 60 years old and above was significantly associated with a shorter LOS (p = 0.05). Conclusion: The majority of HAP cases occurred in men aged 60 years and above. Furthermore, there was a significant relationship between decreased consciousness and increased mortality, as well as between the age of 60 years and above and a shorter LOS.